2016
DOI: 10.1590/1806-9282.62.02.120
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of the consumption of artificial sweeteners - systematic review

Abstract: oBJectiveGuide health professionals and the general public about the use of artificial sweeteners and their consequences for health. MethodologyInclusion and exclusion criteria Studies that evaluated adults and children who used artificial sweeteners compared with individuals who did not were included. As outcome, the adverse clinical effects of this association were analyzed.Exclusion criteria were non-epidemiological and noncomparative studies, and those in disagreement with the inclusion criteria. Databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The higher consumption of artificially sweetened beverages among women with active and past BN and BED [24] might be a reflection of their ED pattern in reducing added sugars. Summarized data from three very large prospective cohort studies showed several risks which were associated with the consumption of artificially sweetened beverages by pregnant women, including prematurity and the diagnosis of asthma in their children up to the age of seven years [43].…”
Section: Discussionmentioning
confidence: 99%
“…The higher consumption of artificially sweetened beverages among women with active and past BN and BED [24] might be a reflection of their ED pattern in reducing added sugars. Summarized data from three very large prospective cohort studies showed several risks which were associated with the consumption of artificially sweetened beverages by pregnant women, including prematurity and the diagnosis of asthma in their children up to the age of seven years [43].…”
Section: Discussionmentioning
confidence: 99%
“…In the EU, the use of LNCS in infant formula, follow-up formula, baby food or/in dietetic foods intended for uses in young children is not permitted except where expressly indicated [ 133 ]. It has been suggested that consumption of LNCS in pregnancy could be associated with increased risk of preterm delivery, asthma, metabolic syndrome and diabetes in the offspring [ 134 , 135 ], although the evidence is also limited. According to regulatory authorities such as FDA and EFSA, the consumption of approved LNCS within the ADI is safe during pregnancy.…”
Section: Dietary Guidelines For Lncsmentioning
confidence: 99%
“…Systematic reviews on cancer risk associated with artificial sweeteners suggest that there is no definitive evidence that LCS increase the risk of cancer incidence. [29][30][31] However, certain studies have produced contradictory results wherein daily large doses of LCS consumption have been associated with bladder cancer. 32 Other significant correlations observed were those between LCS and laryngeal cancer and hematopoietic cancers such as leukemia or lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…33 Daily consumption of soft drinks with added LCS by pregnant women has been reported to increase likelihood of prematurity and development of asthma in children. 31 The adverse effects of LCS may not only be limited to those on the consumer's health but also extend to involve the environment. Regular wastewater treatment procedures are unable to remove these non-nutritive sweeteners effectively from the discharged water.…”
Section: Discussionmentioning
confidence: 99%